Analyzing psychological mechanism of physical activity enhancing Chinese L2 learning efficacy with inhibiting aggressive behavior using cross-lagged panel model - Zixia Bu; Ziqi Gao; Yu Liu; Haohan Yu; Jiyuan Li; Fuqiang Dong; Shan Jiang (PLoS ONE, 2025)
Objective For international students coming to China, the process of learning Chinese is very difficult. At the same time, chronic academic underachievement can lead to aggressive behavior (AB). Although physical activity (PA) has been shown to improve learning performance and psychological well-being, its effectiveness in Chinese language learning and AB has not been clarified. Therefore, the present study examined PA as the main variable and explored its dosage profile in Chinese learning and alleviation of AB. Methods A total of 964 international students from different countries from 8 universities in Beijing were selected as the study population and were assessed using the International Physical Activity Questionnaire (IPAQ), Buss-Perry Aggression Questionnaire (BPAQ) and Hanyu Shuiping Kaoshi (HSK) for 3 longitudinal follow-ups. Analyses of variance, correlations and path models were performed using ANOVA, Pearson and cross-lagged panel model (CLPM). Results High PA level accounted for 18%, moderate PA level for 35%, and light PA level for 47%. PA was significantly elevated on AB and all sub-indicators except HSK (F = 1.58–4.38, η² = 0.03–0.05, P < 0.05), and was decreasingly related to physical aggression, verbal aggression, and angry (F = 4.38, η² = 0.03,; F = 3.24, η² = 0.04,; F = 2.37, η² = 0.04; P < 0.01). In terms of correlation, cross-sectional comparison showed that AB was significantly negatively correlated with both HSK and PA (r = −0.41, P < 0.01; 1 = −0.44, P < 0.01). The longitudinal results showed a decreasing trend of negative correlation between AB and PA under T1-T3 stages (r = −0.29, r = −0.44, P < 0.01), and no significant change in the degree of negative correlation with HSK (r = −0.28, r = −0.35, P < 0.01). The positive correlation between HSK and PA did not change significantly (r = 0.15, r = 0.18, P < 0.01). The positive correlation of PA itself decreased over time (r = 0.83, r = 0.76, P < 0.01). The CLPM results show that under T1 phase, PA negatively affects AB in T1 and T2 phases (β = −0.42, β = −0.18) and positively affects HSK in T2 phase (β = 0.24). AB negatively affects T1 and T2 phase HSK (β = −0.25, β = −0.26). HSK negatively affects AB in T2 phase (β = −0.11). Under T2 phase, PA negatively affects T3 phase AB (β = −0.07) and positively affects T3 phase HSK (β = 0.22). AB negatively affects T3 stage HSK (β = −0.10). HSK negatively influences T3 stage AB (β = −0.08). Conclusions (1) PA may have beneficial effects on both Chinese L2 learning efficacy and the reduction of AB. (2) Higher levels of PA are likely to strengthen these effects. (3) Establishing daily PA habits may serve as an effective strategy to enhance L2 learning outcomes while simultaneously reducing AB in learners.